2014
DOI: 10.1007/s10875-014-9995-5
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Deficiency Secondary to Chronic Lymphocytic Leukemia: Should Patients be Treated with Prophylactic Replacement Immunoglobulin?

Abstract: Hypogammaglobulinemia is a common finding in chronic lymphocytic leukemia (CLL). Its incidence increases with disease duration and stage such that it is present in up to 85 % of patients at some point in their disease course. It is therefore important to monitor patients for the development of an antibody deficiency. However, not all patients with antibody deficiency secondary to CLL are symptomatic with bacterial infections. In addition patients are susceptible to viral, fungal and opportunistic infections as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
101
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(107 citation statements)
references
References 25 publications
0
101
0
6
Order By: Relevance
“…Those infections have traditionally been classified as moderate (that is, requiring oral antibiotics and no hospitalization) or severe (that is, requiring parenteral antibiotics or hospitalization, or both). Before the advent of novel therapeutics, mortality rates of 25%-50% were found to be directly attributable to such infections 7,8 .…”
Section: Infections and Hypogammaglobulinemiamentioning
confidence: 99%
See 2 more Smart Citations
“…Those infections have traditionally been classified as moderate (that is, requiring oral antibiotics and no hospitalization) or severe (that is, requiring parenteral antibiotics or hospitalization, or both). Before the advent of novel therapeutics, mortality rates of 25%-50% were found to be directly attributable to such infections 7,8 .…”
Section: Infections and Hypogammaglobulinemiamentioning
confidence: 99%
“…Infections in patients with cll are paradigmatically bacterial in origin and tend to occur in the respiratory tract; however, they can also affect the skin, gastrointestinal tract, and bloodstream 7 . Before the use of purine analogues, the most frequent bacterial infections included Streptococcus pneumoniae, Staphylococcus aureus, Streptococcus pyogenes, and Escherichia coli 8 .…”
Section: Infections and Hypogammaglobulinemiamentioning
confidence: 99%
See 1 more Smart Citation
“…Malignancies, especially lymphoproliferative disorders (chronic lymphocytic leukaemia (CLL) 9 and myeloma), are commonly associated with hypogammaglobulinaemia. This may be due to the malignancy itself or treatment of the condition.…”
Section: Malignanciesmentioning
confidence: 99%
“…[10][11][12] Attempts have been made to define the risk factors for infections in CLL in order to select patients who could benefit most from IgRT, even with a pre-emptive approach. Dhalla et al 1 suggested that immunization responses could be used to stratify infection risk and select patients for IgRT. Freeman et al 13 proposed that screening patients with CLL for IgG subclass deficiency could be a useful adjunct in stratifying the patients' risk for infection.…”
Section: Letters To the Editormentioning
confidence: 99%